Rehabilitation models of care for children and youth living with traumatic brain and/or spinal cord injuries: A focus on family-centred care, psychosocial wellbeing, and transitions. Issue 4 (21st April 2022) - Botchway, Edith N.; Knight, Sarah; Muscara, Frank; Greenham, Mardee; D'Cruz, Kate; Bonyhady, Bruce; Anderson, Vicki; Scheinberg, Adam
ABSTRACT: To describe current rehabilitation models of care and programmes, in Australia and internationally, related to family-centred care, psychosocial support, and transitions used for children and youth who have sustained major traumatic brain and/or spinal cord injuries. Fourteen services were interviewed, including eight medical rehabilitation services, three community-based rehabilitation services, two insurance services, and one state-wide education service provider. Semi-structured interviews were transcribed and analysed using qualitative content analysis in NVivo. Compared to the number of services supporting children and youth with traumatic brain injury, a very limited number supported those with spinal cord injury. Although valued and often included in the model of care, family-centred care was rarely systematically evaluated by the services. Most services provided psychosocial and transition support to children and youth, and their families in the short-term post-injury, but not in the long-term. Several challenges also hindered the smooth delivery of these support services, including poor communication between service providers. These findings show that services aimed to provide the best possible care to these children and youth, and their families; guided by rehabilitation models of care. However, challenges persist with regards to delivering family-centred care, coordinating return to school, and providing long-term support for psychosocial problems and transition.